Evaluasi Sistem Pengendalian Internal Persediaan Bahan Baku - Agung Ivan Firdaus; Norita Cahya Yuliarti; Ach Syahfrudin Z (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
Internal Control is a process that is controlled by each person in a company to achieve stated objectives such as: complying with regulations and laws, securing company assets and data, accuracy of financial statements and efficiency and operating effectiveness. This research was conducted to evaluate the internal ctheontrol system of raw material inventory which was been applied. Makmur Jaya.the type of research used descriptive is descriptive qualitative research type with case study approuch that describes and explains a problem in systematic and factual so that by collecting information related to the object under study. Data source used in primary and secoundary data source. The data collection technical used are obervations. Interviews and documentantation. Data analisys technique is done by collectiong data, describing the internal control system of raw material inventory applied by the company, then evaluate the internal control system applied. Makmur Jaya based on the control environment, risk assesment, control activities information and communication and monitoring. The results of this study indicate that the internal control sytem applied is bad cause there are double control is one human. Keyword : Internal Control System, Raw Material Inventory